Multimedia Flipbook Development Using the Hannafin and Peck Model in IPAS Learning at MIS Terpadu Langsa - Rizqia, Annisa; Jelita, Jelita; Panjaitan, Chery Julida (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2024)
Students have a significant affinity with digital technology. Therefore, teachers are required to have basic skills in designing and packaging learning that utilizes digital technology to attract and motivate students. This study aims to develop multimedia flipbooks with the Hannafin and Peck model, test the feasibility of the media, and analyze teacher responses and student responses. This research uses the Research and Development (R&D) method with the Hannafin and Peck development model which consists of three phases, namely: (1) needs analysis (analysis); (2) design (design); (3) development (development), implementation (implementation). In the Hannafin and Peck model, all phases involve a process of evaluation and revision. The research subjects were digital fifth grade students of MIS Terpadu Langsa. The results showed that the feasibility of the media can be seen from the average results of validation from the six validators. Material expert validation 94.6% (Very Feasible), media expert validation 95.3% (Very Feasible), language expert validation 82.65% (Very Feasible). Thus it can be concluded that multimedia flipbooks using the Hannafin and Peck model are suitable for use in the learning process for digital fifth grade students of MIS Terpadu Langsa.